2014
DOI: 10.1080/02699931.2014.954529
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pain and the anticipation of pain on temporal perception: A role for attention and arousal

Abstract: The overestimation of the duration of fear-inducing stimuli relative to neutral stimuli is a robust finding within the temporal perception literature. Whilst this effect is consistently reported with auditory and visual stimuli, there has been little examination of whether it can be replicated using painful stimulation. The aim of the current study was, therefore, to explore how pain and the anticipation of pain affected perceived duration of time. A modified verbal estimation paradigm was developed in which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 34 publications
7
70
1
Order By: Relevance
“…There was no difference in duration perception in the unpleasant and control conditions. Taken together with the results of previous research (Ogden, Moore, Redfern, & McGlone, 2015), the results of this study suggest that pleasant and painful somatosensory stimulation have opposing effects on temporal perception, and additionally that pleasant touch can alter aspects of perceptual and attentional processing outside the purely affective domain. …”
supporting
confidence: 73%
See 1 more Smart Citation
“…There was no difference in duration perception in the unpleasant and control conditions. Taken together with the results of previous research (Ogden, Moore, Redfern, & McGlone, 2015), the results of this study suggest that pleasant and painful somatosensory stimulation have opposing effects on temporal perception, and additionally that pleasant touch can alter aspects of perceptual and attentional processing outside the purely affective domain. …”
supporting
confidence: 73%
“…These are exteroceptive emotional triggers relating to stimuli that originate outside the body, but what is less understood is the effect of interoceptive stimuli on interval timing. Negative affective somatosensory stimulation (pain) has been shown to be effective in altering temporal perception (Hare, 1963;Ogden, Moore, Redfern, & McGlone, 2015), but to date no studies have explored whether positive somatosensory stimulation (pleasant touch) influences the perceived duration of time.…”
Section: Introductionmentioning
confidence: 99%
“…For angry facial expressions this pattern has been replicated by the same research group and also, separate research groups (for a review see; Droit-Volet, 2013; Droit-Volet et al, 2013) using different tasks (Gil & DroitVolet, 2011). The overestimation effect generalizes to different types of emotional stimuli including emotional sounds (Noulhiane et al, 2007), aversively conditioned stimuli (Droit-Volet et al, 2010;Ogden et al, 2014), highly arousing negative images (Angrilli et al, 1997;Droit-Volet et al, 2011;Gil & Droit-Volet, 2012;Shi et al, 2012;Smith et al, 2011) and highly feared stimuli (Buetti & Lleras, 2012;Langer et al, 1961;Watts & Sharrock, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Ogden et al (2015a) reported longer duration estimates of short intervals (242-1500 ms) defined by the presentation of visual shapes when the end of the interval was associated with the presentation or the anticipation of a brief (300 ms) thermal painful stimulus (heat pain). This is consistent with earlier work showing that the anticipation of pain leads to longer time estimations (e.g., Hare (1963) using electrical stimulation shocks).…”
Section: Introductionmentioning
confidence: 98%
“…Investigating time perception using thermal modality is challenging because the stimuli onsets and offsets are generally slow using standard thermal induction methods relying on radiant heat or contact heating/cooling Peltier devices (but see Ogden et al (2015a), using a thermoresistor heating element combined with a Peltier device). However, this does not preclude from the investigation of multi-seconds intervals.…”
Section: Introductionmentioning
confidence: 99%